Phlugis ocraceovittata and its ultrasonic calling song (Orthoptera, Tettigoniidae, Phlugidini) - Chamorro-Rengifo, Juliana; Braun, Holger (Zootaxa, 2016)
Some observations on the small predatory katydid Phlugis ocraceovittata Piza 1960 from southern Brazil are presented. A male was calling both day and night, producing long uniformly structured sequences with maximum energy between 40 and 60 kHz. According to anecdotal and indirect evidence the species is not exclusively predacious and can live partly also on vegetable food.